Penerapan Berbagai Inovasi Teknologi yang Mendukung Program Peningkatan Produksi Beras Nasional (P2BN) di Kabupaten Purwakarta (Review) - KARSIDI PERMADI; BAMBANG SUNANDAR (Fakultas Pertanian Universitas Udayana, 2013)
Rice production in Purwakarta district is fairly good because productivity is not low (5.73 t/ha). However, rice cultivation needs improvement so that productivity can be increased. Therefore, BPTP West Java from 2007 to 2012 has conducted several studies of technological innovation in Purwakarta district in an effort to increase rice production. The purpose of this paper is to inform the results of studies that have been conducted by the Ministry of Agriculture in Purwakarta Regency of West Java to support the National Rice Production Enhancement Program (P2BN). Based on the results of the assessment of a range of new varieties (VUB), it was found that Mekongga, Ciherang, Inpari 2 varieties were good and were selected by the farmers in the district of Wanayasa and Pondok Salam. Morevore to support IP-400 rice, no-tillage system (TOT) can shorten the time of land preparation using locally probiotic microbes such as Agri Simba. The dose of Agri Simba used to accelerate the degradation of rice straw was best 10 liters/ha. The application of NPK fertilizer use is more practical than single fertilizer. Morevore the addition of local probiotic (Agri Super) NPK Kujang did not show any interaction effect on rice yield of Inpari 13 variety. The administration of local probiotic Agri Super showed 20% higher yields Agri Simba. The addition of NPK Kujang at 300 kg/ha produced the highest yield at 8.24 tons/ha paddy, and the lowest yield produced by 200 kg/ha NPK approximately at 7.55 tons/ha paddy.